PERBEDAAN GOLONGAN DARAH ABO DI ANEMIA HEMOLITIK AUTOIMUN - Hilma Yuniar; Rachmawati Muhiddin; Mansyur Arif (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2014)
Discrepancy of blood type is the difference result between cell grouping and serum grouping. The technical errors and various conditions are the common cause of their discrepancy, one of the conditions is mentioned as Auto Immune Haemolytic Anaemia (AIHA). Auto immune haemolytic anemia cold type can cause discrepancy due to cold autoantibody reaction. In this study the researchers conducted further testing to determine the actual blood type so the right blood transfusion can be given. A 41 years old woman with weakness and pale since a month before her admission to the present hospital, has been treated in a district hospital with the same condition. On the physical examination, the researchers found hepatomegaly. The complete blood count showed hemoglobin level was 2.1 g/dL and leukocyte count was 21.54×103/uL. The clinical diagnosis made by the emergency department was anemia pro evaluation and planned blood transfusion with 500 cc of PRC. The peripheral blood smear shown hemolytic anemia. The result of the initial blood type test on forward grouping were AB positive agglutination and on reverse grouping O positive, then followed by washing erythrocyte and the researchers found the similar result. Because of the extra antibody found in both examination, the examination was carried out at 37°C of the patient’s temperature. The researchers found that the blood type of AB rhesus positive with cold autoantibody. The indirect coombs test was positive. The patient is had been reported with ABO discrepancy cold type autoantibody (group IV) in autoimmune hemolytic anemia cold type. Further screening antibody tests are needed to confirm the specific antibody.